2016
DOI: 10.21776/ub.apmba.2016.005.02.2
|View full text |Cite
|
Sign up to set email alerts
|

How Brand Trust is Influenced by Perceived Value and Service Quality: Mediated by Hotel Customer Satisfaction

Abstract: This paper examines the effect of perceived value and service quality on brand trust directly and indirectly through customer satisfaction. Brand trust can be defined as the relationship between consumers and the corporate that is based on trust and reliability of its performance. Questionnaires were given to guests of three-star hotels in Malang, Indonesia, with 158 surveys returned and 114 valid responses were analyzed. Reliability and validity were examined first, and partial least squares (PLS-SEM) analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 24 publications
6
17
0
7
Order By: Relevance
“…In this case, the higher the value of a hotel perceived by the customer, the higher the level of customer satisfaction with the hotel. The findings of this study support the results of research conducted on previous hotel customers, such as Milfelner et al (2011), Suhartanto (2011), Gumussoy and Koseoglu (2016), Prameka et al (2016). Thus, it can be concluded that perceived value is an antecedent of satisfaction for hotel customers.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this case, the higher the value of a hotel perceived by the customer, the higher the level of customer satisfaction with the hotel. The findings of this study support the results of research conducted on previous hotel customers, such as Milfelner et al (2011), Suhartanto (2011), Gumussoy and Koseoglu (2016), Prameka et al (2016). Thus, it can be concluded that perceived value is an antecedent of satisfaction for hotel customers.…”
Section: Discussionsupporting
confidence: 90%
“…Based on these findings, it can be concluded that the higher the customer's perception of the service quality of a hotel, the higher the value customers feel towards the hotel offer. The results of this study are in line with the findings of Milfelner et al (2011), Suhartanto (2011), and Sudarso (2015), but are contradictory to the empirical model developed by Prameka et al (2016), namely that service quality and perceived value have no relationship.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In foreign, unlike Russian sources, the issue of trust in the hospitality industry is represented quite widely. A number of authors study the problem of the impact of service quality on brand trust [21,22]. In connection with the active use of Internet technologies in hospitality, issues of establishing trusting relationships between the consumer and the hotel product manufacturer in the online environment are being developed, indicators of customer confidence in the process of online hotel booking are being investigated [23,24,25,26].…”
Section: Literature Reviewmentioning
confidence: 99%